1989
DOI: 10.1084/jem.169.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cellular DNA synthesis by reovirus occurs through a receptor-linked signaling pathway that is mimicked by antiidiotypic, antireceptor antibody.

Abstract: Mammalian reovirus type 3 binds to a 67-kD surface glycoprotein on the membrane of neuronal cells. This interaction initiates the infective reovirus cycle. The physiological function of this virus receptor is not known, however, initial studies illustrate a striking structural and antigenic homology to the beta adrenergic receptor family. The earliest known pathologic effect of reovirus type 3 is an inhibition of host cell DNA synthesis within 8-10 h after virus attachment. The studies reported here demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…This proportion agrees with previous estimates of the mitotic index of 0-2A cells cultured in N2/0.5% FCS (1,29,30,32) (16,17,38). ,8-Adrenergic agonists neither reproduce nor alter Reo3R-mediated inhibition of L-cell proliferation (31). Reo3R ligands do not affect isoproterenol-induced cAMP accumulation (38).…”
Section: Resultssupporting
confidence: 81%
“…This proportion agrees with previous estimates of the mitotic index of 0-2A cells cultured in N2/0.5% FCS (1,29,30,32) (16,17,38). ,8-Adrenergic agonists neither reproduce nor alter Reo3R-mediated inhibition of L-cell proliferation (31). Reo3R ligands do not affect isoproterenol-induced cAMP accumulation (38).…”
Section: Resultssupporting
confidence: 81%
“…This effect is not due to infection of cells, as replication-defective reovirus type 3 particles retain this property (12). We recently have demonstrated that mAb 87.92.6 similarly inhibits DNA synthesis in fibroblasts, neuronal cells, and lymphocytes (13). Data from one such experiment are shown in Fig.…”
mentioning
confidence: 94%
“…However, the degree of cell culture synchronization prior to infection was either incomplete or not specified in these studies, impeding accurate identification of the cell cycle phase affected (14,68). Serotype 3 prototype strains type 3 Dearing (T3D) and type 3 Abney (T3A) inhibit cellular DNA synthesis to a greater extent than the serotype 1 prototype strain type 1 Lang (T1L) in a variety of cell lines (20,23,75,82). Studies using T1L ϫ T3D and T1L ϫ T3A reassortant viruses indicate that the serotype 3 S1 gene is the primary determinant of differences in the capacity of reovirus strains to inhibit DNA synthesis (75,82).…”
mentioning
confidence: 99%
“…The reovirus S1 gene segment is bicistronic, encoding the viral attachment protein, 1, and a non-virion-associated protein, 1s, from overlapping, alternative open reading frames (53). Studies using purified recombinant serotype 3 1 protein and an anti-idiotype antibody (87.92.6) generated against the T3D 1-specific monoclonal antibody 9BG5 suggest that inhibition of DNA synthesis in some cells may result from engagement of a cell surface receptor by 1 (23,(70)(71)(72). For example, treatment of R1.1 thymoma cells with purified T3D 1 results in a reversible G 1 -to-S transition arrest (70,71).…”
mentioning
confidence: 99%